Hubungan Pengetahuan Dengan Kecacingan Pada Anak SD Negeri 108822 Pancur Batu Deli Serdang Sumatera Utara - David Sumanto Napitupulu; Jagentar P Pane; Lindawati Simorangkir (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
Worm is an infection disease caused by the Soil Transmitted Helminth (STH) parasite and is usually found in children. Primary school children are most susceptible to infection with worm parasites due to their habit of playing on the ground with their friends. According to WHO in 2019, the prevalence of Soil Transmitted Helminth worm infection is 24% of the entire population or more than 1.5 million people. The purpose of this study was to determine the relationship between knowledge of primary school children and helminthiasis in children of SD Negeri 108822 Pancur Batu. This study used a correlation method with a cross sectional approach to 40 primary school children respondents. Sampling was done by purposive sampling technique. The results showed that children’s knowledge about helminthiasis in general was good (62.5%). Based on the results of the sedimentation method for worm eggs in the faeces of the participants, it was found that no worm eggs were found. Data were collected using a questionnaire with the Spearman rho statistical test. Measurements using the Spearman rho statistical test obtained a p value = 0.000, which means that there is a relationship between children’s knowledge and the incidence of helminthiasis. Based on the results of the closeness of the relationship, the value of r = -0.590 is negative, meaning that the hidgher the child’s knowledge, the lower the helminthiasis.